Lanthanide Borohydrido Complexes Supported by ansa‐Bis(amidinato) Ligands with a Rigid o‐Phenylene Linker: Effect of Ligand Tailoring on Catalytic Lactide Polymerization. Issue 35 (4th November 2013) - Tolpygin, Aleksei O.; Skvortsov, Grigorii G.; Cherkasov, Anton V.; Fukin, Georgy K.; Glukhova, Tatyana A.; Trifonov, Alexander A.
Abstract: A series of lanthanide monoborohydrido complexes C6 H4 ‐1, 2‐[NC(R)NR′]2 Ln(BH4 )(L) n (Ln = Y, Nd, Sm; R = t Bu, Ph; R′ = 2, 6‐Me2 C6 H3, SiMe3 ; L = dme = dimethoxyethane, n = 1; L = thf, n = 2), in which lanthanides are coordinated by bulky ansa ‐bis(amidinato) ligand systems with a conformationally rigid o ‐phenylene linker (C6 H4 ‐1, 2‐[NC(R)NR′]2 2– ), were synthesized by the salt metathesis reactions of equimolar amounts of Ln(BH4 )3 (thf)3 and C6 H4 ‐1, 2‐[NC(R)NR′]2 X2 (thf) n (X = Li, Na) in thf. X‐ray diffraction studies revealed that the complexes are monomeric. Depending on the denticity of the donor ligand (L = dme or thf), the terminal borohydrido ligand coordinated to the metal ion can be located in either an equatorial (L = thf) or an apical (L = dme) position. All complexes are efficient catalysts for the ring‐opening polymerization of rac ‐lactide, which allows to convert up to 1000 equiv. of monomer into a polymer at room temperature within 10–150 min and affords atactic polylactides with high molecular weights and moderate molecular‐weight distributions (1.28–2.16). Yttrium–borohydrido complexes coordinated by the C6 H4 ‐1, 2‐[NC( t Bu)N(2, 6‐Me2 C6 H3 )]2 2– ligand system showed enhanced catalytic activity compared to that of the analogue complexes containing the C6 H4 ‐1, 2‐[NC(Ph)NSiMe3 ]2 2– ligand. The obtained borohydrido complexes catalyze the hydrophosphonylation of benzaldehyde at room temperature with good reaction rates. Abstract : The replacement of two molecules of monodentate thf by one bidentate dme ligand in the coordination sphere of yttrium results in the migration of a borohydrido ligand from an equatorial position to an apical one.